Tìm hiểu tính cách nhân vật Bá Kiến thông qua nghĩa tình thái của câu =Exploring the characteristics of Ba Kien by means of modeality of sentences /Nguyễn Thị Nhung, - Nguyễn, Thị Nhung.
: By analyzing the modality of sentences in the language of the author and the language of characters, focusing on three conversations between Ba Kien and Chi Pheo, Ba Kien’s Characteristics are clearly portrayed. Therefore, it gives us more understanding of modality, philosophical, moral and educational values of Chi Pheo and Nam Cao’s gift of writing.